PENGGUNAAN MEDIA AUDIO VISUAL ANIMASI KARTUN UNTUK MENUMBUHKAN MOTIVASI BELAJAR SISWA KELAS 3 SEKOLAH DASAR - Lestari Nur Fitriani; Yulina Ismiyanti; Sari Yustiana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Learning is influenced by various factors, one of which is student motivation. Many students struggle with abstract subjects like mathematics due to unengaging teaching methods. Using audiovisual media, particularly animated cartoons, can capture students' attention and enhance their learning motivation. This study aims to examine the effect of using animated cartoon audiovisual media on the learning motivation of third-grade elementary school students in mathematics. The research employs a qualitative approach with a case study method conducted at SDN Waru. Data were collected through observations, interviews, and documentation, then analyzed using data triangulation techniques. The findings indicate that students show increased enthusiasm and engagement in mathematics learning after the implementation of animated cartoon audiovisual media. Teachers report that students who were previously passive become more active and interested in learning. Additionally, parents note that their children demonstrate greater enthusiasm for studying at home. Despite these benefits, challenges such as infrastructure limitations and teachers’ proficiency in using media still exist. This study concludes that animated cartoon audiovisual media can be an effective tool to enhance students’ motivation, provided that adequate facilities and teacher training are in place.